Pyriproxyfen, villain or good guy? A brief review - Andressa Pereira Cabral; Fabrício Pereira dos Santos Maia; D’Angelo Carlo Magliano; Jones Bernardes Graceli; Paula Soares; Eduardo Andrés Rios Morris; Leandro Miranda-Alves (Archives of Endocrinology and Metabolism)
ABSTRACT Pyriproxyfen (PPF) acts as a juvenile growth regulator, interfering with normal metamorphosis and blocking the development of insects into adulthood. Although the World Health Organization (WHO) considers the use of PPF at a concentration of 0.01 mg/L as unlikely to pose health risks, recent studies have unveiled potential risks associated with PPF exposure to non-target organisms. Exposure to PPF disrupts insect development primarily by mimicking juvenile hormones; therefore, concerns linger over its impact on unintended species. Studies have highlighted the adverse effects of PPF on aquatic invertebrates, fish, and amphibians and revealed mortality and developmental abnormalities in non-target mosquito species exposed to PPF-treated water. Moreover, PPF may act as an endocrine disruptor, interfering with hormonal pathways crucial for growth, reproduction, and behavior in exposed organisms. Amphibians, for instance, display altered reproductive physiology and developmental abnormalities due to disruptions in endocrine signaling pathways caused by PPF. The ecological ramifications of PPF extend beyond direct toxicity to non-target species. Indirect effects include shifts in food web dynamics and ecosystem functioning. Reductions in insect populations, induced by PPF, can disrupt food availability for higher trophic levels, potentially destabilizing community structure and ecosystem equilibrium. Given mounting evidence of unintended consequences, robust risk assessment and regulatory oversight are imperative. Accurate classification of PPF by regulatory bodies is essential to balancing its role in disease control and pest management benefits with the need to safeguard non-target species and maintain ecosystem health. Future research must prioritize comprehensive assessments of PPF's ecological impact across various habitats and taxa to inform evidence-based policymaking.